2016
DOI: 10.1002/micr.30021
|View full text |Cite
|
Sign up to set email alerts
|

The double stitch everting technique in end‐to‐side vascular anastomoses

Abstract: A wealth of modifications of the original end-to-side technique 1 are described in the literature, but so far no human randomized study has shown the superiority of one technique over another. 2 To answer the needs of reduced time and increased efficiency, we devised the "double stitch everting technique." Leaving the needle in situ in the vessel wall in order to help with the tying of the final two knots, also known as the "modified Harashina procedure" has already been described. 3 For this technique, the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The DSE technique was described in our group's previous publication. 11 Our research revealed that most time was lost when performing a microvascular anastomosis in-between suture tying, during needle loading and unloading. We evolved the modified Harashina procedure by proposing that before each knot is tied, the needle is ran through the vessel wall and left in place.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…The DSE technique was described in our group's previous publication. 11 Our research revealed that most time was lost when performing a microvascular anastomosis in-between suture tying, during needle loading and unloading. We evolved the modified Harashina procedure by proposing that before each knot is tied, the needle is ran through the vessel wall and left in place.…”
Section: Methodsmentioning
confidence: 85%
“…Notice the improvement of suture symmetry. Source: Reproduced with permission from Volovici et al 11 significant (p < 0.001, logistic regression) when adjusted for the level of experience (►Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
“…the journal. Our enthusiasm was somewhat dampened, nonetheless, when we realized that the technique they describe had already been published by us in the same journal in 2016 (Volovici et al, 2017). We coined this technique the double stitch everting, because it implies a double throw of the needle which, positioned and left in place inside the vessel wall, helps ensure proper wall eversion.…”
mentioning
confidence: 99%